2017
DOI: 10.1037/cap0000082
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of student satisfaction in a large psychology undergraduate program.

Abstract: Psychology is one of the most popular undergraduate majors in North America, yet few studies have examined psychology majors' views of their degree program. The purpose of the present study was to identify the factors that contribute to students' satisfaction with their psychology degree. The participants were psychology majors (N ϭ 237) graduating from a large Canadian undergraduate program. Three cohorts of graduating students (classes of 2013, 2014, and 2015) completed a comprehensive exit survey. Multiple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 67 publications
2
23
0
1
Order By: Relevance
“…One reason for the difference in expectations could be the fact that a part-time student cannot fully appreciate all the facilities that the full-time students have more time to access (Moro-Egido and Panades, 2010). Of course, there can be various other reasons for the part-time students' more negative evaluations of the education service quality performance, including the greater imbalance between the competing demands of work and college that they experience, and the more personal and family challenges (Sears et al, 2017) they undergo, compared to full-time students. Despite this, the part-time students made significantly more recommendations of the service to others (H14), including work colleagues.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One reason for the difference in expectations could be the fact that a part-time student cannot fully appreciate all the facilities that the full-time students have more time to access (Moro-Egido and Panades, 2010). Of course, there can be various other reasons for the part-time students' more negative evaluations of the education service quality performance, including the greater imbalance between the competing demands of work and college that they experience, and the more personal and family challenges (Sears et al, 2017) they undergo, compared to full-time students. Despite this, the part-time students made significantly more recommendations of the service to others (H14), including work colleagues.…”
Section: Discussionmentioning
confidence: 99%
“…The strongest approach to this would be longitudinally following the same students through their university life. In addition, although this study argues that students are not normally knowledgeable enough about the subject-related educational provision to assess it (Driscoll and Wicks, 1998), and so they rely more on the tangibles to draw conclusions about overall quality (Hoffman and Kretovics, 2004), a future study could examine student perspectives on education provision while taking into account their views on the intangibles like core subject content and career information relating to the taught programme, Sears et al (2017) did this with a similar sample to the current study, comprising of undergraduate psychology students in Canada.…”
Section: Limitations and Future Directionsmentioning
confidence: 97%
See 1 more Smart Citation
“…Even for relatively brief service encounters, these expectations and evaluations are multidimensional, as indicated by the ServQual instrument (Parasuraman, Berry, & Zeithaml, 1991), which operationalizes expectancy-disconfirmation along five dimensions: reliability (in performing the service to standard), assurance (trust in the provider's knowledge; their courtesy), tangibles (facilities, materials and personnel), empathy ("caring, individualized attention"), and responsiveness ("willingness to help"; Parasuraman et al, 1991, p. 41). In exploring the satisfaction of international students, such multidimensional assessment reveals a broad range of factors relevant to their experience in the host country (Sears et al, 2017), some of which lie beyond what an institution would traditionally consider to be the service they provide. These may include the way that students are received outside the institution by members of the host community, the local availability of familiar foods, and off-campus shopping and entertainment.…”
Section: Literature Review the Nature Of Satisfactionmentioning
confidence: 99%
“…There are various aspects that might contribute to student satisfaction. Students' expectation of college life (Arambewela and Hall 2009), teaching quality (Sears et al 2017), socializing and sense of community (Andrea and Benjamin 2013), as well as students' perceived stress, humor and social skills (Rezaei and Jeddi 2020) were found to be associated with their overall satisfaction. Particularly, Elliott and Shin (2002) found that valuable course content, excellence of instruction, and being able to take desired classes are important variables and significantly predicted students' satisfaction.…”
Section: Introductionmentioning
confidence: 99%